Black tent housing nomads in compliance with sustainable development (Identification and investigation criteria) - Eskandari, Mahdi; Mehdipour Rabori, Fatemeh (Pure and Applied Science Advances, 2017)
Architecture is not static position of shape or location; it is living phenomenon only through human activity meaning. The machine age and subsequent change in thoughts and insights toward life and art has caused the valuable place of vernacular architecture like other arts lowered and its values be ignored; however, today, architecture technology development on the one hand and the value and importance of sustainable development on the other hand has caused using sustainable architecture and its exploitation in compliance with contemporary architecture and architectural principles of permanent and temporary human settlements between engineers and architects become a great competition. Common vernacular architecture among nomad's tribes, such as Eskimos architecture and residents of coldest and warmest parts of the Amazon rainforest in the world is considered an example of architecture and environmental compatibility in the warm and desert Iranian habitats that is in full compliance with what we today refer to as sustainable architecture. This article begins with summarizing definitions expanding with principles and the diverse opinions on the issue of sustainable development and vernacular architecture of nomadic settlements (black tent).